Remaking Public Politics? New Municipalism, participatory governance and urban welfare in Barcelona - van Dyk, Silke; Gerstenhöfer, Luzie Sophia (PARTECIPAZIONE E CONFLITTO, 2026)
Municipalist movements have sought to respond to multiple crises under conditions of aus-terity. The best-known example is the movement party Barcelona en Comú, which for eight years turned the Catalan capital into a flagship of new urban politics. A novel alliance between the municipalist government and civil society aimed to challenge the dominance of private economic interests and the austerity policies of the national government. In doing so, it sought not only to address widespread social precarity but also to transform the very practice of politics. Although social rights and precarity were central concerns of the protest movements that brought Barcelona en Comú to power, comprehensive analyses of municipalist social policy remain scarce, with the partial exception of housing. By focusing on social policy under municipalist governance in Barcelona, this article thus highlights an understudied policy field. Adopting a multi-sited approach across four domains—basic social protection, dental care, energy rights, and home care services—the article examines how politics have been reshaped in these areas, paying particular attention to civic participation and to the relations between the municipality, the central state, and the private sector.